Mid-infrared emissive InAsSb quantum dots grown by metal–organic chemical vapor deposition - Tang, Xiaohong (2016)
InAsSb islands/quantum dots (QDs) emitting at wavelength >2.8 μm were self-assembled on InP substrate by using metal–organic chemical vapor deposition (MOCVD). Instead of using arsine, the safer organic tert-butylarsine (TBAs) was used as the arsenic source in the growth process. Effects of the growth conditions, i.e. substrate temperature and the growth rate, on the InAsSb QD formations have been studied. A narrow temperature window from 450 °C to 470 °C was found for growing high quality InAsSb QDs. InAsSb rings instead of islands/dots were formed using the conventional Stranski–Krastanow (S–K) growth mode if the growth rate was low or if InAsSb was grown for a longer time. By increasing the V : III ratio for the InAsSb growth, InAsSb islands/dots were formed with the same growth rate. To reduce the dot size and increase the InAsSb QD density, an alternative interruption growth (AIG) method was proposed and investigated. Using the AIG growth method, much higher dot density of the InAsSb QDs has been achieved, about 3 × 109 cm−2, which is about 10 times of that of the QDs grown by using the conventional S–K growth method. Strong photoluminescence emissions of the InAsSb islands/dots were observed. At room temperature, the emission wavelength of the InAsSb islands/dots was measured at >2.8 μm.